Ripensare l’agente morale. Al di là di analitici e continentali - Fabris, Adriano (Filosofia Morale/Moral Philosophy, 2022)
In this paper I will first offer a brief analysis of the scenario in which moral philosophy is developed in the contemporary debate. I will start by pointing out the dissatisfaction with the way in which it is categorized today and therefore I will try to show some emerging trends, related to theoretical and practical issues, that need to be urgently addressed. Then, given this conceptual background, I will identify a line of research which appears not only implicit in the current developments of the discipline, but, above all, crucial to explore today and in the future. We must, in fact, examine the autonomous action of artificial devices from a moral point of view and develop an ethics of the relationship with them. In this perspective I will try to address the ambiguity I mentioned in the first part of the article and I will offer my contribution to manage it.